2015
DOI: 10.1007/s10397-015-0904-6
|View full text |Cite
|
Sign up to set email alerts
|

Natural orifice transluminal endoscopic surgery (NOTES) salpingectomy for ectopic pregnancy: a first series demonstrating how a new surgical technique can be applied in a low-resource setting

Abstract: This paper demonstrates the feasibility of a salpingectomy for ectopic pregnancy by transvaginal natural orifice transluminal endoscopic surgery (vNOTES).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 18 publications
(22 reference statements)
1
3
0
Order By: Relevance
“…The mean duration of surgery was 43.4 ± 12.6 (range, 22–68; median 42) in this study. Based on the data from our series and previous reports, 10,11,14 it can be said that vNOTES salpingectomy is not associated with longer operating times compared to single port or conventional laparoscopy.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…The mean duration of surgery was 43.4 ± 12.6 (range, 22–68; median 42) in this study. Based on the data from our series and previous reports, 10,11,14 it can be said that vNOTES salpingectomy is not associated with longer operating times compared to single port or conventional laparoscopy.…”
Section: Discussionsupporting
confidence: 58%
“…The self‐constructed pessary port we utilize is similar to the glove port used by several authors 14,15 . The addition of the pessary eliminates the need for a wound retractor, further reducing the cost and increasing accessibility.…”
Section: Discussionmentioning
confidence: 99%
“…The transvaginal natural orifice transluminal endoscopic surgery (vNOTES) is a new minimally invasive procedure (MIP) in which the vagina is used as a natural access to the peritoneal cavity and enables endoscopic surgery with conventional laparoscopic instruments. Several studies have demonstrated the feasibility and safety on vNOTES with many advantages leading to a day-care or ambulatory procedure: reduced immediate postoperative pain, faster postoperative recovery, better cosmetic results without skin scar, high patient satisfaction [1][2][3][4][5][6][7][8][9][10][11]. Some studies have also shown the superiority of vNOTES in comparison with the classical laparoscopic surgery in term of lower postoperative pain scores and the absence of trocar-site complications [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…It is advised to perform a careful vaginal examination before performing this procedure (13) . vNOTES salpingectomy, which can be performed successfully in women diagnosed with ectopic pregnancy, can be used safely in heterotopic pregnancy as seen in our case (15,16) . Although heterotopic pregnancy is quite rare, it should always be in the differential diagnosis of acute abdomen of pregnant patients.…”
Section: Discussionmentioning
confidence: 81%